AUTOIMAGEM GENITAL, FUNÇÃO SEXUAL E DESCONFORTO NO ASSOALHO PÉLVICO EM MULHERES JOVENS UNIVERSITÁRIAS: GENITAL SELF-IMAGE, SEXUAL FUNCTION AND PELVIC FLOOR DISCOMFORT IN YOUNG UNIVERSITARY WOMEN (Revista Contexto & Saúde, 2022)
Introduction: Women with negative genital self-image may have sexual dysfunction (SD). Still, SD can be related to discomfort in the pelvic floor. Objective: To investigate the relationship between genital self-image, sexual function and discomfort in the pelvic floor in young university women. Methods: Observational and cross-sectional study with 102 undergraduate and graduate students between 18 and 29 years old, sexually active. An identification form, the Female Sexual Function Index (FSFI), Pelvic Floor Distress Inventory (PFDI-SF-20) and Female Genital Self-Image Scale (FGSIS) questionnaires were applied. Results: The total FGSIS score indicated positive genital self-image, FSFI good sexual function and PFDI-20 discomfort in the low pelvic floor. There was a positive relationship between genital self-image and sexual function and an inverse relationship with discomfort in the pelvic floor. Conclusion: Women had positive genital self-image, good sexual function and low discomfort in the pelvic floor, and the variables were related to each other.